Hypoxic Preconditioning Maintains GLT-1 Against Transient Global Cerebral Ischemia Through Upregulating Cx43 and Inhibiting c-Src - Li, Kongping; Zhou, Huarong; Zhan, Lixuan; Shi, Zhe; Sun, Weiwen; Liu, Dandan; Liu, Liu; Liang, Donghai; Tan, Yafu; Xu, Wensheng; Xu, En (Frontiers in Molecular Neuroscience, 2018)
Transient global cerebral ischemia (tGCI) causes excessive release of glutamate from neurons. Astrocytic glutamate transporter-1 (GLT-1) and glutamine synthetase (GS) together play a predominant role in maintaining glutamate at normal extracellular concentrations. Though our previous studies reported the alleviation of tGCI-induced neuronal death by hypoxic preconditioning (HPC) in hippocampal CA1 of adult rats, the underlying mechanism has not yet been fully elaborated. In this study, we aimed to investigate the roles of GLT-l and GS in the neuroprotection mediated by HPC against tGCI and to ascertain whether these roles can be regulated by connexin 43 (Cx43) and c-Src activity. We found that HPC decreased the level of extracellular glutamate in CA1 after tGCI via maintenance of GLT-1 expression and GS activity. Inhibition of GLT-1 expression with dihydrokainate (DHK) or inhibition of GS activity with methionine sulfoximine (MSO) abolished the neuroprotection induced by HPC. Also, HPC markedly upregulated Cx43 and inhibited p-c-Src expression in CA1 after tGCI, whereas inhibition of Cx43 with Gap26 dramatically reversed this effect. Furthermore, inhibition of p-c-Src with 4-amino-5-(4-chlorophenyl)-7-(t-butyl) pyrazolo (3, 4-d) pyrimidine (PP2) decreased c-Src activity, increased protein levels of GLT-1 and Cx43, enhanced GS activity, and thus reduced extracellular glutamate level in CA1 after tGCI. Collectively, our data demonstrated that reduced extracellular glutamate induced by HPC against tGCI through preventing the reduction of GLT-1 expression and maintaining GS activity in hippocampal CA1, which was mediated by upregulating Cx43 expression and inhibiting c-Src activity.